2016
DOI: 10.1177/1049732316657812
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Life Histories of Pregnant-Involved Young Aboriginal Women With Substance Use Experiences in Three Canadian Cities

Abstract: Despite attention paid to substance use during pregnancy, understandings of young Aboriginal women's experiences based on their perspectives have been virtually absent in the published literature. This study's objective was to understand the life experiences of pregnant-involved young Aboriginal women with alcohol and drugs. Semi-structured interviews to gather life histories were conducted with 23 young Aboriginal women who had experiences with pregnancy, and alcohol and drug use. Transcribed interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 34 publications
3
65
0
Order By: Relevance
“…They suggested that providers should also be educated, so that they share in this deeper understanding about the role of alcohol in perpetuating the intergenerational trauma of colonization, carrying the damage of the past forward and continuing to harm AI/AN people in the present. These findings correspond to those in the published research that explores similar issues (Shahram, S. Z., Bottorff, J. L., Kurtz, D. L. M., Oelke, N. D... (2016) In sum, participants did not see substance use as an isolated incident, but as a behavioral outcome resulting from the interconnected cycle of historical trauma, reduced social and familial support, increased substance use, and contemporary trauma. Therefore, an FASD prevention program in an urban AI/AN community is unlikely to be effective if it focuses solely on: (1) intervening at the time of pregnancy; (2) preventing a substance-exposed pregnancy through the practice known as screening brief intervention and referral to treatment (SBIRT); and 3prescription of a long-acting contraceptive method if substance use cannot be prevented while a woman is sexually active.…”
Section: Discussionsupporting
confidence: 87%
“…They suggested that providers should also be educated, so that they share in this deeper understanding about the role of alcohol in perpetuating the intergenerational trauma of colonization, carrying the damage of the past forward and continuing to harm AI/AN people in the present. These findings correspond to those in the published research that explores similar issues (Shahram, S. Z., Bottorff, J. L., Kurtz, D. L. M., Oelke, N. D... (2016) In sum, participants did not see substance use as an isolated incident, but as a behavioral outcome resulting from the interconnected cycle of historical trauma, reduced social and familial support, increased substance use, and contemporary trauma. Therefore, an FASD prevention program in an urban AI/AN community is unlikely to be effective if it focuses solely on: (1) intervening at the time of pregnancy; (2) preventing a substance-exposed pregnancy through the practice known as screening brief intervention and referral to treatment (SBIRT); and 3prescription of a long-acting contraceptive method if substance use cannot be prevented while a woman is sexually active.…”
Section: Discussionsupporting
confidence: 87%
“…Mobile phones were also seen as an opportunity to support health and well-being in the context of pregnancy and parenting. Previous Cedar research among young Indigenous mothers observed that being able to parent their children was key to participants’ own wellness, while those whose children had been taken into care expressed feelings of deep regret and loss [ 41 ]. Participants in this study included pregnant mothers preparing for birth, parents of children currently in care of the state who were interested in visitation and regaining custody, and parents with custody of children who were navigating ongoing relationships with social workers as well as trying to protect their children’s health and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Further, highlighting the structural and social determinants of substance use provides actionable targets for interventions that can support women and their children. Importantly, by including the variables in this analysis related to women’s socio-political-historical contexts, we were able to present a fuller depiction of women’s actual lives, in keeping with previous qualitative findings from work with this same population [ 23 , 24 ]. Indeed, a common criticism of quantitative research is its inability to produce rich and contextualized data.…”
Section: Discussionmentioning
confidence: 64%